Is SARS-CoV-2 an Etiologic Agent or Predisposing Factor for Oral Lesions in COVID-19 Patients? A Concise Review of Reported Cases in the Literature - Shahroo Etemad-Moghadam; Mojgan Alaeddini (International Journal of Dentistry)
The pathogenic mechanism of SARS-CoV-2 infection is unclear, and its symptoms vary in different patients. Initial reports of COVID-19 concentrated on pulmonary issues, but with time, additional features such as hyposmia/anosmia, dysgeusia, and skin lesions were added to the list of COVID-19 symptoms. There have been an increasing number of reports on oral cavity lesions in individuals with COVID-19, which might be relevant considering that this location is one of the first sites coming into contact with the virus and that it contains the SARS-CoV-2 receptor. We hereby aim to familiarize practicing head and neck clinicians with the range of oral lesions reported in COVID-19 patients and to critically appraise the most recent data on the role of SARS-CoV-2 in these lesions. We also discuss the ongoing debate on the direct/indirect association of oral symptoms with the disease. COVID-19 cases with simultaneous oral symptoms were extracted from the literature, and articles discussing the role of SARS-CoV-2 in oral lesions were compiled and methodically analyzed. We found approximately 95 COVID-19 patients with a wide range of oral lesions. Based on current evidence, the exact role of SARS-CoV-2 in the development of oral lesions remains unclear. Oral examination of patients is needed to provide adequate cases for analysis to clarify unknown problems related to COVID-19. There is evidence to support both the direct and indirect roles of SARS-CoV-2 in the development of oral lesions. Awareness of the possibility of oral manifestations in COVID-19 is important to clarify the range of disease signs and symptoms.